Os sentidos do multiculturalismo nas políticas-práticas curriculares no contexto da formação do/a pedagogo/a. - Andrade., Raisa Albuquerque (2013)
This study aimed to investigate how the curricular policies are (re) interpreted to approach multiculturalism within the initial training process educators / the Education Center at the Federal University of Paraíba (CE / UFPB) - Campus I. Thus, we listed the following specific objectives: to analyze the statements allowing the insertion of multiculturalism in political texts guiding the initial training process Educators / the CE / UFPB; identify the meanings attributed to multiculturalism in political pedagogical project of the pedagogy course analyze the possible presence of multiculturalism in the curriculum components of the pedagogy course UFPB. The theoretical approach was anchored in critical perspective, being based on Candau (2008), and Sacavino Candau (2011), Freire (1991, 1996, 2001, 2011), McLaren (1997), Moreira (1996, 1999), and Morgado (2010). Referenced are still authors who advance the critical perspective and offer some support for the understanding of multiculturalism in other perspectives, such as Hall (2009), Fleuri (2003.2009) and Miskolci (2012). The analyzes were supported by the approach of the continuous cycle of policies proposed by Ball and Bowe (1992) and subsequently deepened by Ball (1994, 2009). The analytical focus of this influence was the context, the context of text production and the context of practice. At first, we exposed the meanings, the semantic universe as well as the diverse perspectives of multiculturalism for understanding the philosophical and epistemological assumptions that guide the object of study. Subsequently, we sought to punctuate the object of study within the contexts analyzed, ie, were highlighted major national and international influences that supported the inclusion of multiculturalism in education policy in order to present how the context of influence is reflected in the context production of text and dialogue and are reinterpreted in the context of practice. From the analysis, it was identified that multiculturalism has senses hybrids in political texts. In the local context, it is revealed within a disciplinary logic, however, the disciplines that enable the integration of multiculturalism into the curriculum not have the same importance as components that address the knowledge regarding the skills and competencies. Whereas multiculturalism was integrated into the Faculty of Education at the disciplinary logic, we analyzed the configuration assume that the disciplines in the context of practice, as a result, we found that different meanings are attributed to multiculturalism. Thus, in line with Ball (2009) policies are not simply constructed and implemented, taking into account that different interpretations are made from political texts, like a play in which there is the text, however, the piece takes when life is represented.